Old Ship of Zion : the Afro-Baptist Ritual in the African Diaspora. - Pitts, Walter F. (Religion in America (New York, N.Y.), 1996)
Following the author's fieldwork in black Baptist churches in Texas, he retraces the African origins of African-American forms of worship. His historical comparisons and linguistic analyses uncover striking parallels between "Afro-Baptist" services and religious rituals in West and Central Africa